Self-reported campus alcohol policy and college alcohol consumption: a multilevel analysis of 4592 Korean students from 82 colleges - Sarah Soyeon Oh; Yeong Jun Ju; Sung-in Jang; Eun-Cheol Park (BMC, 2020)
Abstract Background Campus alcohol policy has been associated with student alcohol consumption in numerous studies. However, more information is required to assess the extent to which school policy affects student drinking behavior; especially when both individual-level sociodemographic characteristics of students and area-level characteristics of college campuses are controlled for. Thus, this paper explores the association between campus alcohol policy and student alcohol consumption among a nationally representative sample of college students in South Korea, while controlling for both individual and area-level characteristics. Methods We surveyed and analyzed the data of 4592 students from 82 colleges. Multilevel (hierarchical) linear modeling was used to identify the association between campus alcohol policy and alcohol consumption levels, measured via the AUDIT-C (Alcohol Use Disorders Identification Test - Consumption). Controlled individual-level characteristics included sex, year level, major, GPA (grade point average), pocket money, smoking status, stress level, depressive thoughts, suicidal thoughts, and number of clubs/organizations. Controlled area-level characteristics included college type, number of students, number of faculty members, number of workers/administrators, and region. Results Compared to students unaware of their school's campus alcohol policy, students who self-reported that their campuses allow drinking in outdoor spaces (β = 0.755 p = 0.010) or in all areas (β = 0.820, p = 0.044) had higher AUDIT-C scores. Students attending schools with a large number of students, males, freshmen, students with low GPA, students with high amounts of pocket money, and smokers also had higher alcohol consumption scores relative to their peers. Alcohol education experience in the form of lectures, mail, and/or campaigns were not associated with student alcohol consumption levels. Conclusion Our results suggest an association between self-reported campus alcohol policy and student alcohol consumption. College educators and administrators must be aware that relative to students unaware of their school's campus alcohol policy, students at colleges that allow drinking in outdoor spaces or all areas consume higher amounts of alcohol than their peers; even when area-level factors are controlled for. Trial registration Yonsei IRB (IRB number: Y-2017-0084). https://irb.yonsei.ac.kr Date of registration: 01/2017. Date of enrolment of first participant to trial: 03/01/2017. Y-2017-0084.